Association between neutrophil-to-albumin ratio and mortality in patients with cardiogenic shock: a retrospective cohort study. Issue 10 (19th October 2020) - Peng, Yangpei; Xue, Yangjing; Wang, Jinsheng; Xiang, Huaqiang; Ji, Kangting; Wang, Jie; Lin, Cong
Abstract : Objectives: To investigate the prognostic value of neutrophil-to-albumin ratio (NAR) in critically ill patients with cardiogenic shock (CS). Design: A retrospective cohort study. Setting: A single centre in Boston, USA. Participants: 475 patients with CS were included, among which 272 (57.3%) were men and 328 (69.1%) were white. Primary and secondary outcome measures: The primary outcome was 90-day mortality and the secondary outcomes were 30-day and 365-day mortality. Results: A significant positive correlation between NAR levels and 90-day, 30-day or 365-day mortality was observed. For 90-day mortality, the adjusted HR (95% CI) values given NAR levels 23.54–27.86 and >27.86 were 1.71 (1.14 to 2.55) and 1.93 (1.27 to 2.93) compared with the reference (NAR<23.47). Receiver operator characteristic curve analysis showed that NAR had a certain prognostic value in predicting 90-day mortality of CS, which was more sensitive than the neutrophil percentage or the serum albumin level alone (0.651 vs 0.509, 0.584). For the secondary outcomes, the upward trend remained statistically significant. Conclusions: NAR level was associated with the mortality of CS patients. The prognostic value of NAR was more sensitive than the neutrophil percentage or the serum albumin level alone, but not as good as Sequential Organ Failure Assessment or Simplified Acute Physiology Score.